Requirement of Protein Synthesis for Bacteriophage φX174 Superinfection Exclusion - Hutchison, Clyde A. (1971)
Within 5 to 10 min at 37 C, bacteria infected by bacteriophage φX174 acquire the ability to exclude superinfecting φX particles from reproducing themselves. The superinfecting phage are blocked at a stage prior to synthesis of the parental replicative form molecule; the superinfecting deoxyribonucleic acid remains as intact (infective) single strands. Establishment of superinfection exclusion and its maintenance require protein synthesis.